En ordbog er en brugsgenstand, en god ordbog er indrettet til sit specielle formål - Bergenholtz, Henning (Nordiske Studier i Leksikografi, 2010)
A dictionary is a tool. Most dictionaries are constructed as polyfunctional tools: A dictionary is a dictionary or a dictionary is to be used by everyone for every kind of communicative and cognitive problem. Normal tools are not polyfunctional. If you go to a shop and ask for a saw, you have to specify first what you are going to saw: a big tree or a small piece of plywood. You will be offered a monofunctional saw. A good tool is a tool conceived for a certain function and for a certain user group for certain needs. This paper will argue for the need of dictionary conceptions for monofunctional dictionaries giving examples from four dictionaries with fixed expression.